2021
DOI: 10.1161/jaha.121.023054
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Factors Mediate the Association Between Serum Uric Acid to Serum Creatinine Ratio and Cardiovascular Disease

Abstract: Background The serum uric acid/serum creatinine ratio (SUA/SCr), which represents renal function‐normalized SUA, is associated with diverse adverse outcomes. The aim of this study was to investigate the association between SUA/SCr and cardiovascular disease (CVD), and determine whether and to what extent this association is mediated by cardiometabolic factors. Methods and Results This prospective study enrolled 96 378 participants from the Kailuan study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
0
24
1
Order By: Relevance
“…Previous studies on biomarkers of acute exacerbation of chronic obstructive pulmonary disease mostly focused on inflammatory factors, such as TNF- α and IL-6, and rarely involved other biomarkers. A study of 96,378 patients showed that the CMI level was negatively correlated with cardiac function and positively correlated with the risk of cardiovascular disease [ 13 ]. In the study of 11,345 participants, CMI level was shown to be an independent influencing factor for future heart disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on biomarkers of acute exacerbation of chronic obstructive pulmonary disease mostly focused on inflammatory factors, such as TNF- α and IL-6, and rarely involved other biomarkers. A study of 96,378 patients showed that the CMI level was negatively correlated with cardiac function and positively correlated with the risk of cardiovascular disease [ 13 ]. In the study of 11,345 participants, CMI level was shown to be an independent influencing factor for future heart disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum creatinine (SCr), a biosynthetic product of phosphocreatine metabolism in muscle, is widely used in clinical practice to assess renal function and is more direct and readily available than glomerular filtration rate (GFR). Several clinical studies have shown that even within the normal range, higher SCr is strongly associated with the risk of several diseases, such as cardiovascular disease and diabetes [ 16 , 17 ]. Currently, few clinical studies have investigated the relationship between HS and SCr levels and HS-accompanied fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“… 36 Wang et al performed a nationwide study and reported that SUA/SCr was positively associated with cardiovascular disease and partially mediated by metabolic factors. 14 However, studies regarding SUA/SCr and stroke recurrence among young adults were limited.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that SUA/SCr was associated with metabolic and cardiovascular diseases. 14 However, few studies have explored the potential role of SUA/SCr among young patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%